Casual Store Surabaya Marketing Communication Through Shopee Marketplace In Maintaining Consumer Loyalty - Darmawan, Muhammad Alif; Hariyanto, Didik (Universitas Muhammadiyah Sidoarjo, 2024)
Marketing communication strategy is a way to consume products to the target market in order to achieve the company's goals. Through marketing communication strategies, companies try to disseminate information, influence, persuade and remind target messages about the company and the products offered by the company can be accepted. This study uses a descriptive qualitative research type. This study aims to determine the marketing communication strategy of the Casual Surabaya shopee marketplace in maintaining consumer loyalty. With data collection techniques carried out by observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation and drawing conclusions. The results of the study show that brands and products most often use marketing communication strategies, such as utilizing their features such as Store Promo features, Discount Packages, Store Coupons, Store Vouchers, Shopee live and Seller Chat Of course, these strategies are very important to maintain brand and product loyalty among consumers.